Thermodynamic guidelines for improved operation of iron-based catalysts in gasification of biomass. (1st April 2023) - Ruivo, Luís; Silva, Tiago; Neves, Daniel; Tarelho, Luís; Frade, Jorge
Abstract: The present work intended the development of a graphical approach to support the operation of conventional iron-based catalysts under gasification conditions. A combination of experimental data and thermodynamic modelling was used as guidelines to elucidate the dependence of catalyst performance on the thermochemical conditions of producer gas. The outcomes are represented by stability diagrams in a form of planar representations for easier identification of appropriate operating windows. Attention was focused not only on potential deactivation mechanisms resulting from gas-solid interactions, but also on the stability of relevant catalytic phases when exposed to biomass-derived gas atmospheres at temperatures in the range 600–900 °C. The results suggest that controlled process parameters contributes to enhance the tolerance of iron-based materials to deactivation by carbon deposition, H2 S poisoning and/or carbonation. Selected examples also show that the redox potential imposed by producer gas can have a significant impact on the stability of relevant active phases, with subsequent impact on catalyst performance. To overcome these constrains, one should considerer suitable composition changes to enhance their redox properties, possibly combined with microstructural or nanostructural development during materials processing. Highlights: A graphical approach was proposed to support the operation of Fe-based catalysts. Experimental data and thermodynamic modelling were used as guidelines. The redox potential of producer gas can have a significant impact on the stability of catalyst. Controlled process parameters allow to enhance the resistance of catalysts to deactivation.